Combined Effect of Stray Current and Sustained Compressive Loading on Chloride Transport in Concrete. (25th September 2021) - Ni, Yuancheng; Zhu, Eryu
Abstract : As with the leakage of stray current in the surrounding medium, the chloride transport in concrete is influenced by the stray current and loading of the subway structure. This paper presents the results of the experimental study on the chloride transport properties of concrete under the combined action of stray current and sustained compressive loading. First, an experiment was setup to explore the chloride transport in the subway structure as the concrete specimen embedded with steel under test current and study the influence of the existence of steel on the chloride transport profiles in concrete under stray current. Then, to investigate the combined effect of stray current and loading on the chloride transport properties, an improved experiment was designed with stray current and sustained compressive loading. The chloride transport profiles were measured, respectively, subjected to different stray currents and compressive stress levels. The experimental results indicated that stray current and sustained compressive loading have a significant influence on the chloride transport properties of concrete, and the loading threshold existed as the turning point of the chloride transport rate. Based on the experimental data and migration theory, the prediction model of chloride transport in concrete under stray current and sustained compressive loading was established and verified by the experimental measurements, and the steel corrosion-induced cover cracking was studied, and the comparison indicated that the numerical results were consistent with the experimental results.